A study on diffusion of H atoms in solid parahydrogen: Physics in Quantum Crystals - Fushitani*, Mizuho; Momose, Takamasa (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2003)
Diffusion of hydrogen atoms in solid parahydrogen was investigated using high-resolution infrared spectroscopy. Hydrogen atoms were produced as by-products of a photoinduced reaction ofnitric oxides embedded in solid parahydrogen. The diffusion of the hydrogen atoms is mainly terminatedby the reaction of H + NO → HNO. The diffusion rate determined from the increase of the intensity of rotation-vibration transitions of HNO molecules was found to be two orders of magnitudelarger than that determined by the self-recombination reaction of H + H → H2 in pureparahydrogen crystals.